Experience capitalization: Information we might otherwise have missed - Gbakie, Emmanuel Sahr (Technical Centre for Agricultural and Rural Cooperation, 2019)
I was officially introduced to the experience capitalization approach at a CTA-organised workshop for the anglophone countries in West Africa in Ghana, back in March, 2017. This followed up on a two-day meeting organised by a consultant in Sierra Leone a month beforehand. During the workshops our team was introduced to the methodology and saw how the experience capitalization documentation process differs from standard monitoring and evaluation. We also covered the concepts behind writing articles based on our work for wider dissemination to interested parties.